2017
DOI: 10.1097/brs.0000000000001857
|View full text |Cite
|
Sign up to set email alerts
|

One-Level Lumbar Degenerative Spondylolisthesis and Posterior Approach: Is Transforaminal Lateral Interbody Fusion Mandatory?

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 60 publications
3
48
0
Order By: Relevance
“…A better understanding of the complications rate of and risk factors for unplanned reoperations may help improve surgical outcomes and prognoses. It was reported that the cumulative reoperation rate in lumbar degenerative diseases was 4.7% at 3 months, 6.1% at 1 year, 8.5% at 2 years, 15.2% at 3 years, 17.7% at 5 years and 23.3% (38/163 patients) at the final follow-up [ 4 8 ]. Reducing the rate of lumbar surgery revision is also vital because the outcomes of DLS reoperation may be worse than the results of the initial surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the complications rate of and risk factors for unplanned reoperations may help improve surgical outcomes and prognoses. It was reported that the cumulative reoperation rate in lumbar degenerative diseases was 4.7% at 3 months, 6.1% at 1 year, 8.5% at 2 years, 15.2% at 3 years, 17.7% at 5 years and 23.3% (38/163 patients) at the final follow-up [ 4 8 ]. Reducing the rate of lumbar surgery revision is also vital because the outcomes of DLS reoperation may be worse than the results of the initial surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…Endler et al, [18] , in their prospective study reported a 51.25% improvement in ODI score in PLF group. Challier et al, [19] in their RCT, reported that ODI scores improved by 19 in the PLF group. Etemadifar et al, [20] in their RCT, observed that ODI improved by 53.2% in the PLF group.…”
Section: Discussionmentioning
confidence: 93%
“…We had a significant improvement in clinical outcome and we analyzed if the radiological outcome in terms of fusion supported it. Challier et al's RCT [19] reported a fusion rate of 56.7% in the PLF group. Lee et al's study [21] showed a fusion rate of 89.7% at 2 year follow up in PLF group Levin et al, 2018 [22] , in their meta-analysis of 2 RCT's and 5 cohort studies, reported that the pooled fusion success rate was 84.7% in the PLF group of patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…81 A systematic review and meta-analysis by Levin et al comparing PLF with transforaminal lumbar interbody fusion (TLIF) from five observational studies, also favoured TLIF for achieving improvement in ODI and back pain and better fusion rates. 82 However, these findings have been challenged by a recent RCT with two-year follow-up, which has found no additional benefit of TLIF over PLF with regard to clinical or radiographic alignment parameters despite a better fusion rate, 83 with similar findings reported in a retrospective cohort study by Fujimori et al 84 Furthermore, a systematic review and meta-analysis by McAnany et al, comparing the effectiveness of PLF and interbody fusion from five observational studies, has found no difference in clinical outcome (ODI, Short Form-36 [SF-36], VAS score), fusion rates or complication rates. 85…”
Section: Operative Managementmentioning
confidence: 99%